Vertically Aligned 2D/3D Pb-Sn Perovskites with Enhanced Charge Extraction and Suppressed Phase Segregation for Efficient Printable Solar Cells - Li, Chaohui; Pan, Yamin; Hu, Jinlong; Qiu, Shudi; Zhang, Cuiling; Yang, Yuzhao; Chen, Shi; Liu, Xianhu; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; Mai, Yaohua; Guo, Fei (ACS Energy Letters, 2020)
The concept of mixed 2D/3D heterostructures has emerged as an effective method for improving the stability of lead halide perovskite solar cells, which has been, however, rarely reported in lead-tin (Pb-Sn) mixed perovskite devices. Here, we report a scalable process for depositing mixed 2D/3D Pb-Sn perovskite solar cells that deliver remarkably enhanced efficiency and stability compared to their 3D counterparts. The incorporation of a small amount (3.75%) of an organic cation 2-(4-fluorophenyl)ethylammonium iodide induces the growth of highly oriented Pb-Sn perovskite crystals perpendicularly aligned with the substrate. Moreover, for the first time, phase segregation is observed in pristine 3D Pb-Sn perovskites, which is suppressed due to the presence of the 2D perovskites. Accordingly, a high current density of 28.42 mA cm(-2) is obtained due to the markedly enhanced spectral response and charge extraction. Eventually, mixed 2D/3D Pb-Sn perovskite devices with a band gap of 1.33 eV yield efficiencies as high as 17.51% and in parallel exhibit good stability.
Created from Fastlane, WoS look-up